Pengaruh Pendidikan Kesehatan Reproduksi tentang Pernikahan Dini Terhadap Pengetahuan dan Sikap Remaja - Nurannisa Fitria Aprianti; Nurlathifah N. Yusuf; Eka Faizaturrahmi (Journal of Pharmaceutical and Health Research, 2022)
Background : In Indonesia, there are more than one million women aged 20-24 whose first marriage occurred at the age of less than 18 years (1.2 million people). Early marriage is carried out by someone who is under the age of 19 and is not ready in various aspects of marriage. This is likely to have an impact on reproductive health for both men and women. Objective : to determine the effect of reproductive health education on early marriage on the knowledge and attitudes of adolescents in the working area of ​​the twin bridge health center in 2022. Methods : Pre Experimental research design with one group pretest-Posttest study in March-July 2022. The population in this study was male and female youth. The number of samples in this study were 30 respondents. The sampling technique uses stratified random sampling. The instrument in this study used a questionnaire. Data analysis used the Wilcoxon statistical test. Result: there is an effect of reproductive health education about early marriage on knowledge p 0.00 < α 0.05 and attitude .00 < α 0.05 adolescents in the working area of ​​the twin bridge health center. Conclucion : Reproductive health education about early marriage in adolescents influences the knowledge and attitudes of adolescents